Removal Mechanism of As(III) by a Novel Fe−Mn Binary Oxide Adsorbent: Oxidation and Sorption - Zhang, Gao-Sheng; Qu, Jiu-Hui; Liu, Hui-Juan; Liu, Rui-Ping; Li, Guo-Ting (Environmental science & technology, 2007)
A novel Fe−Mn binary oxide adsorbent was developed for effective As(III) removal, which is more difficult to remove from drinking water and much more toxic to humans than As(V). The synthetic adsorbent showed a significantly higher As(III) uptake than As(V). The mechanism study is therefore necessary for interpreting such result and understanding the As(III) removal process. A control experiment was conducted to investigate the effect of Na2SO3-treatment on arsenic removal, which can provide useful information on As(III) removal mechanism. The adsorbent was first treated by Na2SO3, which can lower its oxidizing capacity by reductive dissolution of the Mn oxide and then reacted with As(V) or As(III). The results showed that the As(V) uptake was enhanced while the As(III) removal was inhibited after the pretreatment, indicating the important role of manganese dioxide during the As(III) removal. FTIR along with XPS was used to analyze the surface change of the original Fe−Mn adsorbent and the pretreated adsorbent before and after reaction with As(V) or As(III). Change in characteristic surface hydroxyl groups (Fe−OH, 1130, 1048, and 973 cm-1) was observed by the FTIR. The determination of arsenic oxidation state on the solid surface after reaction with As(III) revealed that the manganese dioxide instead of the iron oxide oxidized As(III) to As(V). The iron oxide was dominant for adsorbing the formed As(V). An oxidation and sorption mechanism for As(III) removal was developed. The relatively higher As(III) uptake may be attributed to the formation of fresh adsorption sites at the solid surface during As(III) oxidation.